A comparative study of the stimuli‐responsive properties of DMAEA and DMAEMA containing polymers. Issue 16 (6th June 2013) - Cotanda, Pepa; Wright, Daniel B.; Tyler, Martin; O'Reilly, Rachel K.
ABSTRACT: Reversible addition‐fragmentation chain transfer copolymerization of dimethylaminoethyl acrylate (DMAEA) and methyl acrylate (MA) and their methacrylate counterparts (MMA) has been performed with good control over molecular weight and polydispersity. A screening in composition of copolymers has been performed from 0 to 75% of MA (or MMA). The behavior of these pH and temperature‐sensitive copolymers has been studied in aqueous solution by measuring the cloud point (CP) and the acid dissociation constants (p K a ). The higher incorporation of the hydrophobic monomer in the copolymer resulted in an increase in the p K a values due to the larger distance between charges thus facilitating the protonation of adjacent nitrogens for both, the acrylate and methacrylate derivatives. The CP behavior of the copolymers has been studied in pure water and the CP values have been found to be irreproducible for the acrylate polymers, as a consequence of the self‐hydrolysis of DMAEA. Hence, kinetic studies have been performed to quantify the degree of self‐hydrolysis at different temperatures and polymer concentrations to explore the full potential and application of these versatile polymers. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3333–3338 Abstract : Reversible addition‐fragmentation chain transfer copolymerization of dimethylaminoethyl acrylate and methyl acrylate and their methacrylate counterparts has been performed with good control over molecular weight and polydispersity. The behavior of these pH and temperature‐sensitive copolymers has been studied in aqueous solution by measuring the stability, cloud point and the acid dissociation constants (p K a ). Interestingly a higher incorporation of hydrophobic monomer in the copolymer resulted in an increase in the p K a values.